DESIGNING AUTHENTIC ASSESSMENT MODEL FOR WRITING SKILL AT JUNIOR HIGH SCHOOL STUDENTS - Sahyoni Sahyoni (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
Assessing writing is one of the difficulties most English teachers face. Compared to other English skills, writing is generally regarded as the most complicated skill. The media for assessing writing should preferably cover several principles to face this challenge, one of which is authenticity. Authentic assessment is a form of assessment that connects learners to actual life and promotes the fair exploration of three domains. The main objective of this research is to design authentic assessment model for assessing writing skill at junior high school students. This research utilized Research and Development approach which carried out the first years students of Islamic Junior High school (MTsN) Batusangkar and two English teachers as participants. In gaining data, researcher used questionnaire and structured interview. The questionnaire consisted of 30 question related to the authentic assessment. In order to dig deep data related to writing assessment for junior high school students, researchers used unstructured questions. The finding revealed that the personal report is ideally an effective authentic evaluation model for assessing students' writing skills, especially for junior high school students.